A scalar analysis of polarity contrasts between exclusive modifiers - Fagen, Lucas (Proceedings of the Amsterdam Colloquium, 2022)
The English exclusive only licenses weak NPIs like any and ever, but its lexical cousins just, merely, exclusively, and solely do not. This paper sketches an analysis in which only’s status as an NPI licensor follows from its capacity to order alternatives by entailment. NPIs are contradictory with just and merely, which order alternatives by rank, and exclusively and solely, which exclude unordered alternatives.